Clinical Burden of Kala-azar in Bangladesh: A Review Update - Habib, ZH; Yusuf, M Abdullah; Ahmed, I; Jhora, ST (Journal of Science Foundation, 2014)
Kala-azar is a tropical disease. There are an estimated 500,000 new cases of VL and more than 50,000 deaths from the diseases each year. The majority (>90%) of cases occur in just six countries like Bangladesh, India, Nepal, Sudan, Ethiopia and Brazil. Severe VL epidemics have been reported in the past. Since 1990, South Asia has experienced a resurgence of the lethal parasitic disease visceral leishmaniasis (VL). The disease has been reported from 109 districts of three countries. An estimated 190 million people are at risk of infection. The actual incidence rate of the disease is estimated to be about 8-10 times higher than the reported one in all three countries. There is an increasing trend of VL cases in India and fluctuating trends were found in Nepal and Bangladesh. Multi centric studies were conducted in Bangladesh, India and Nepal and major findings were that the current burden of disease is 20 times higher than the elimination target in 2010/2015. Kala-azar has appeared to have spread along the courses of the Ganges and Brahmaputra rivers. In these early outbreaks, the case-fatality rate was reported to be >95 percent, with community-wide mortality rates of >25 percent. This review has focused on the clinical burden of kala-azar in Bangladesh. DOI: http://dx.doi.org/10.3329/jsf.v10i2.17960 J Sci Found, 2012;10(2):70-79